Antifouling low-pressure highly permeable single step produced loose nanofiltration polysulfone membrane for efficient Erichrome Black T/divalent salts fractionation. Issue 4 (August 2022) - Baig, Nadeem; Matin, Asif.; Faizan, M.; Anand, Deepak; Ahmad, Irshad; Khan, Safyan A.
Abstract: Nanofiltration (NF) membranes are effective in treating wastewater containing organics, dyes, and divalent salts; however, lacking the capability of fractionating the dyes/divalent salts, which is crucial for the treatment of the textile wastewater. Loose NF with excellent permeability is highly required to effectively fractionate the dye and divalent salts. Herein, a facile surface modification of ultrafiltration (UF) membranes with the loose layer of nanosilver immobilized polydopamine have been reported. The self-initiated dopamine polymerization on the polysulfone (PS) coordinated with the silver (Ag) to form a loosely held layer of the silver immobilized polydopamine functionalized polysulfone membrane (L -Ag-PDA-PS-membrane). The original polysulfone membrane had a contact angle of 65° that was reduced to 25° after nanosilver immobilization. Fabricated membranes were thoroughly investigated by Fourier-transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), X-ray photoelectron spectroscopy (XPS), Atomic force microscopy (AFM), and contact analyzer. High rejection of 99.9% of Eriochrome Black T (EBT) was witnessed with the exceptionally high permeation flux of 39.2 LMH using L -Ag-PDA-PS-membrane. The polydopamine (PDA)-silver modified membranes showed higher permselectivity than the PDA-only counterparts, the former rejecting the dye altogether while letting most of the divalent ions (Mg 2+, SO4 2- ) pass through. Long-term fouling runs in the presence of bovine serum albumin (BSA) showed that the presence of Ag/PDA slowed down the rate of flux decline considerably, and flux decline was only 15.6% after 6 h of continuous operation in the presence of the foulants. The designed membrane is an excellent example for fractionating the dye and divalent salts. Graphical Abstract: ga1 Highlights: A loose antifouling NF membrane developed for highly efficient EBT/salt fractionation. The water contact angle on the modified surface was observed at 25° A high fractionation of EBT/MgSO4 with 100% rejection of EBT. High permeation flux of 39.2 Lm −2 h −1 bar −1 was observed during the separation of the EBT.